Mouse model of Alzheimer's disease demonstrates differential effects of early disease pathology on various brain regions. Issue 7 (9th March 2021) - Deng, Liting; Gupta, Vivek K.; Wu, Yunqi; Pushpitha, Kanishka; Chitranshi, Nitin; Gupta, Veer B.; Fitzhenry, Matthew J.; Moghaddam, Masoud Zabet; Karl, Tim; Salekdeh, Ghasem Hosseini; Graham, Stuart L.; Haynes, Paul A.; et al.
Abstract: Different parts of the brain are affected distinctively in various stages of the Alzheimer's disease (AD) pathogenesis. Identifying the biochemical changes in specific brain regions is key to comprehend the neuropathological mechanisms in early pre‐symptomatic phases of AD. Quantitative proteomics profiling of four distinct areas of the brain of young APP/PS1 mouse model of AD was performed followed by biochemical pathway enrichment analysis. Findings revealed fundamental compositional and functional shifts even in the early stages of the disease. This novel study highlights unique proteome and biochemical pathway alterations in specific regions of the brain that underlie the early stages of AD pathology and will provide a framework for future longitudinal studies. The proteomics data were deposited into the ProteomeXchange Consortium via PRIDE with the identifier PXD019192.